Aspidosperma (Apocynaceae) plant cytotoxicity and activity towards malaria parasites. Part I: Aspidosperma nitidum (Benth) used as a remedy to treat fever and malaria in the Amazon - Julia Penna Coutinho; Anna Caroline Campos Aguiar; Pierre Alexandre dos Santos; Joaquim Corsino Lima; Maria Gabrielle Lima Rocha; Carlos Leomar Zani; Tania Maria Almeida Alves; Antonio Euzebio Goulart Santana; Maria de Meneses Pereira; Antoniana Ursine Krettli (Memorias do Instituto Oswaldo Cruz, 2013)
Infusions of Aspidosperma nitidum (Apocynaceae) wood bark are used to treat fever and malaria in the Amazon Region. Several species of this family are known to possess indole alkaloids and other classes of secondary metabolites, whereas terpenoids, an inositol and the indole alkaloids harmane-3 acid and braznitidumine have been described in A. nitidum . In the present study, extracts from the wood bark, leaves and branches of this species were prepared for assays against malaria parasites and cytotoxicity testing using human hepatoma and normal monkey kidney cells. The wood bark extracts were active against Plasmodium falciparum and showed a low cytotoxicity in vitro, whereas the leaf and branch extracts and the pure alkaloid braznitidumine were inactive. A crude methanol extract was subjected to acid-base fractionation aimed at obtaining alkaloid-rich fractions, which were active at low concentrations against P. falciparum and in mice infected with and sensitive Plasmodium berghei parasites. Our data validate the antimalarial usefulness of A. nitidum wood bark, a remedy that can most likely help to control malaria. However, the molecules responsible for this antimalarial activity have not yet been identified. Considering their high selectivity index, the alkaloid-rich fractions from the plant bark might be useful in the development of new antimalarials.